(untitled) (Bangladesh Journal of Zoology, 2010)
The abundance and community structure of microorganisms associated with the commercial brands of brine shrimp, Artemia, cysts were studied in a microbiologically-monitored controlled environment for hatching the cysts. The cysts, treated with chlorine, showed no presence of microorganisms during the pre-hatching stage, contrary to those which were untreated; indicating the surface adhering of microorganisms with the cysts. Interestingly, microorganisms were isolated from both the chlorine-treated and untreated cysts when they were hatched. The isolated microorganisms were identified by microscopic, biochemical and cultural properties, and some of them were found potentially pathogenic. This indicates the association of bacteria with Artemia during its encapsulation stage, which is released once the cysts are hatched. This is a cause of concern of introducing bacterial diseases in shrimp hatcheries of Bangladesh during feeding the shrimp larvae. Bangladesh J. Zool. 38(1): 41-49, 2010